2019
DOI: 10.1186/s13059-019-1644-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined single-cell profiling of expression and DNA methylation reveals splicing regulation and heterogeneity

Abstract: BackgroundAlternative splicing is a key regulatory mechanism in eukaryotic cells and increases the effective number of functionally distinct gene products. Using bulk RNA sequencing, splicing variation has been studied across human tissues and in genetically diverse populations. This has identified disease-relevant splicing events, as well as associations between splicing and genomic features, including sequence composition and conservation. However, variability in splicing between single cells from the same t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 38 publications
2
67
1
Order By: Relevance
“…An important conclusion from this study is that DNA methylation, that at best was considered as a way of fine-tuning alternative splicing, may for small number of genes, have an impact such that the level of DNA methylation present inside the body of these genes can have predictive value when estimating the splicing isoforms produced in a given cell type. This is further supported by a recent study showing that splicing variations at the single cell level can be accurately predicted based on local DNA methylation (Linker et al, 2019). Another intriguing possibility, and perhaps a more interesting one, is that these predicTable genes may serve as sensors of DNA methylation to adapt gene expression to external cues (Fig.…”
Section: Genes Subject To Dna Methylation-dependent Splicing In Diffesupporting
confidence: 55%
“…An important conclusion from this study is that DNA methylation, that at best was considered as a way of fine-tuning alternative splicing, may for small number of genes, have an impact such that the level of DNA methylation present inside the body of these genes can have predictive value when estimating the splicing isoforms produced in a given cell type. This is further supported by a recent study showing that splicing variations at the single cell level can be accurately predicted based on local DNA methylation (Linker et al, 2019). Another intriguing possibility, and perhaps a more interesting one, is that these predicTable genes may serve as sensors of DNA methylation to adapt gene expression to external cues (Fig.…”
Section: Genes Subject To Dna Methylation-dependent Splicing In Diffesupporting
confidence: 55%
“…This unexpected result contrasted with previous single molecule imaging studies of several alternative exons that showed that cell-to-cell variability is minimized and tightly regulated by the splicing machinery in single cells [10]. This led to investigations of the mechanisms that might be responsible for stochastic splicing variability among apparently homogeneous cells, such as variation in DNA methylation [11].…”
Section: Introductioncontrasting
confidence: 58%
“…We used our simulator to investigate how the observed inclusion (Ψ) of cassette exons differs from the underlying Ψ, setting the average capture rate to 10% and the other technical parameters to values that are characteristic of Smart-seq2 datasets (see methods). We considered either a bimodal and binary regime of Ψ (i.e., both isoforms are expressed in the population, but rarely by the same cell; Figure 2b), or a non-binary regime (cells tend to express both isoforms; Figure 2c) [5,11,21]. We simulated the splicing of cassette exons in 500 genes, in a population of 300 single cells.…”
Section: Simulations Of Rna Sequencing Reveal Technical Sources Of DImentioning
confidence: 99%
See 2 more Smart Citations